A 79‐year‐old woman with atrial fibrillation and new onset of heart failure. (22nd March 2019) - Schneider, Birke; Nazarenus, Dirk; Stöllberger, Claudia
Abstract: As an alternative to oral anticoagulation, percutaneous left atrial appendage (LAA) closure is an increasingly performed procedure to prevent arterial embolism in patients with non‐valvular atrial fibrillation. Besides procedure‐related complications, residual leaks, device‐related thrombus formation, and dislocation of the LAA occluder have been observed during follow‐up. Heart failure as a consequence of interventional LAA closure has not been reported so far. This case report describes a 79‐year‐old lady with permanent non‐valvular atrial fibrillation presenting with New York Heart Association Class IV heart failure. Symptoms had started immediately after attempted LAA closure 11 months before. Transoesophageal echocardiography demonstrated two devices in the LAA, a large peri‐device leak, a mobile LAA thrombus, a right atrial appendage thrombus, and shunting via a patent foramen ovale. Under a maximally tolerated dose of heart failure medication and edoxaban, the patient remains without bleeding or embolism in New York Heart Association Class II. Because of its unique anatomical and endocrine properties, the LAA plays an important role in situations of pressure and volume overload. Interventional LAA closure interacts unfavourably with left atrial compliance and reservoir function. Atrial and brain natriuretic peptide secretion is known to be significantly reduced after LAA closure. Both mechanisms may result in the development of heart failure. Attempted LAA closure—instead of being the solution—may create new serious problems. Development of heart failure should be assessed, and a systematic search for late leaks after LAA closure should be performed in trials investigating safety and efficacy of this intervention.